Understanding technology adoption practices among Malaysian home grown food and beverage franchisors to foster business growth - Nurul Ashykin Abd Aziz,; Mohd Hizam Hanafiah,; Puteri Fadzline Muhamad Tamyez,; Mohamad Rohieszan Ramdan,; Nur Nabila Huda Sabaran, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Recently, franchising has emerged as a prominent avenue for business expansion, attracting numerous entrepreneurs in local and international markets. While the prevalence of franchise businesses continues to rise, some businesses struggle to achieve growth due to their failure to leverage technology effectively, thereby failing to distinguish themselves from competitors. To remain competitive, franchisors must embrace technology in franchise operations. However, existing literature predominantly focuses on technology utilisation within SMEs, with limited insights into its application within the franchise sector. More importantly, studies on technology adoption practices within the Malaysian franchise industry remain insufficient for business growth. Understanding Malaysian franchisors' technology adoption guide strategies for competitive market edge and sustained growth. The present study aims to fill this gap by exploring the technology adoption practices of Malaysian franchisors through qualitative analysis of six franchisor companies. Data collected through focus group discussion and analysed using thematic analysis revealed four key themes: Product Management, Training and Support, Business Communication, and Performance Monitoring. A new conceptual model for technology adoption in Malaysian franchising is proposed, contributing fresh insights to the field. These findings can inform policymakers, agencies, and franchise investors, enhancing strategies and programs to boost the franchise sector in Malaysia.